2015
DOI: 10.5194/hessd-12-6755-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributed model of hydrological and sediment transport processes in large river basins in Southeast Asia

Abstract: Abstract. Soil erosion and sediment transport have been modeled at several spatial and temporal scales, yet few models have been reported for large river basins (e.g., drainage areas > 100 000 km2). In this study, we propose a process-based distributed model for assessment of sediment transport at a large basin scale. A distributed hydrological model was coupled with a process-based distributed sediment transport model describing soil erosion and sedimentary processes at hillslope units and channels. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Damming is one of the possible causes of sediment load reduction in many rivers worldwide [1,7,9,31,[59][60][61][62]. The Bhumibol Dam on the Ping River and the Sirikit Dam on the Nan River was estimated to cause a 75-85% sediment reduction to the CPR system.…”
Section: Effect Of the Bhumibol Dam On Sediment Supplied To The Chao Phraya Rivermentioning
confidence: 99%
“…Damming is one of the possible causes of sediment load reduction in many rivers worldwide [1,7,9,31,[59][60][61][62]. The Bhumibol Dam on the Ping River and the Sirikit Dam on the Nan River was estimated to cause a 75-85% sediment reduction to the CPR system.…”
Section: Effect Of the Bhumibol Dam On Sediment Supplied To The Chao Phraya Rivermentioning
confidence: 99%
“…Difficulties in the calibration and validation stages of models are other issues to be considered (Aksoy, ). Despite of all these challenges and difficulties, sediment transport models developed at hillslope and watershed scales (Zhang et al, ; Aksoy & Kavvas, ; Arguelles et al, ; Zuliziana et al, ) have enhanced the understanding of the mechanism of sediment transport under varying conditions over the hillslope or watersheds. When the GIS technology is combined with the sediment transport modelling, it is possible to derive an effective way to map spatial distribution of soil erosion risks in large areas to be used in assisting conservation management and land use planning (Mandal & Sharda, ; Dai et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of large dam construction on significant reduction in riverine sediment supply from many rivers to the ocean have been intensively reported during the past decades [7,47,[66][67][68][69][70][71]. In Thailand, many studies suggested a 75-85% sediment reduction in the CPR system due to the Bhumibol Dam in the Ping River and the Sirikit Dam in the Nan River, resulting in severe coastal erosion in the upper Gulf of Thailand.…”
Section: Effect Of Major Dam Construction On Sediment Supplied To the Chao Phraya Rivermentioning
confidence: 99%